Scaling ratios for spectral accelerations caused by seismic site effect under site condition classifications in China - Wang, Yushi; Ding, Yi; Li, Xiaojun (Frontiers in Earth Science, 2023)
The spectral accelerations (Sa), which are widely used as ground motion inputs in structural seismic designing, are significantly affected by local site conditions classified by near-surface geology. A novel approach of quantifying the scaling ratios for Sa on site class I, II, III, and IV under the site condition classifications in Chinese seismic codes, was proposed. In this integrated approach, the scaling ratios for Sa on each site class were subordinated to three constituents, i.e., scaling ratios for peak ground acceleration (PGA), scaling ratios for PGA-normalized Sa, and nonlinear decay exponents. The scaling ratios for PGA were derived from recent studies and numerical simulations of 1,138 borehole models in China, the scaling ratios for PGA-normalized Sa were derived from 3,584 strong motion records in NGA West 2 database, and the nonlinear decay exponents were derived from about 140 thousand borehole observation data recorded by KiK-net. Consequently, this approach was solidly based on statistics of observation data in company with numerical simulations, which resulted in more reasonable and more reliable scaling ratios for Sa caused by the seismic site effect under site condition classifications in China.